Evolution of Time Preferences and Attitudes toward Risk - Netzer, Nick (American Economic Review, 2009)
This paper explores a general model of the evolution and adaption of hedonic utility. It is shown that optimal utility will be increasing strongly in regions where choices have to be made often and decision mistakes have a severe impact on fitness. Several applications are suggested. In the context of intertemporal preferences, the model offers an evolutionary explanation for the existence of conflicting short- and long-run interests that lead to dynamic inconsistency. Concerning attitudes toward risk, an evolutionary explanation is given for S-shaped value functions that adjust to the decision maker's environment. (JEL D81, D83)